Life style associated risk factors of CAD and the effectiveness of an educational intervention on prevention and management of modifiable risk factors of CAD among police personnel in Mysuru city - N, Vasantha.; M Thomas,, Usha; Williams, Sheela; Devi MK, Ashwathy (Indian Journal of Nursing Sciences, 2024)
Background: CAD is predicted to be the most common cause of death globally including India by 2020. CAD is a condition that develops due to the accumulation of atherosclerotic plaque in the pericardial coronary arteries leading to myocardial ischemia. Aim and objectives: To assess the lifestyle associated risk factors of CAD and the effectiveness of an educational intervention on prevention and management of modifiable risk factors of CAD among police personnel Mysuru city. Methods: Research design adopted for the study was exploratory survey in phase I and pre experimental, one group pre test - post test design in the phase II. Non-probability Convenience sampling technique was used to select the 60 police personnel. In phase I, lifestyle associated risk factors were assessed by using lifestyle risk assessment tool for CAD. In phase II, knowledge of police personnel regarding prevention and management of modifiable risk factors of CAD was assessed using SKQ. Educational intervention on prevention and management of modifiable risk factors of CAD was done for police personnel. Results: The study revealed that educational intervention on prevention and management of modifiable risk factors of CAD was effective in enhancing the knowledge of police personnel as indicated by significant at 0.05 level of significance (‘t’=13.8;p<0.05). There was no statistically significant association between the knowledge and selected personal variables of police personnel. Conclusion: Educational intervention was effective in increasing the knowledge of police personnel regarding prevention and management of modifiable risk factors of CAD.